2021
DOI: 10.53555/eijas.v7i1.74
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Entamoeba Gingivalis and Trichomonas Tenax Among Healthy and Patients With Periodontal Disease in Benghazi – Libya.

Abstract: The oral cavity of human is colonized by many microorganisms among these Trichomonas tenax and Entamoeba gingivalis, is known as common parasite of oral cavity and sub maxillary glands especially with poor oral hygiene and presence of periodontal disease. This paper describes the prevalence and patterns of Entamoeba gingivalis and Trichomona stenaxin person with and without periodontitis in Benghazi, Libya, emphasizing on the gender, age, pH of the saliva, smoking habit. Methods Bio film and saliva samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…This results were compatible with the results from Iraq where the prevalence of E. gingivalis was 8% among healthy individuals [19], and India, with a rate of 4% among healthy controls [20]. Since, E. gingivalis detected in the buccal cavity of healthy individuals, some researchers suppose that this parasite could be opportunistic, that is, capable of proliferating in a gingival environment modified by periodontal disease [9,13]. In addition, Hassan et al [15] concluded that the high occurrence of E. gingivalis among diseased groups compared to the healthy group could be related to the presence of genetic variants for E. gingivalis rather than the immune status of the individuals.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This results were compatible with the results from Iraq where the prevalence of E. gingivalis was 8% among healthy individuals [19], and India, with a rate of 4% among healthy controls [20]. Since, E. gingivalis detected in the buccal cavity of healthy individuals, some researchers suppose that this parasite could be opportunistic, that is, capable of proliferating in a gingival environment modified by periodontal disease [9,13]. In addition, Hassan et al [15] concluded that the high occurrence of E. gingivalis among diseased groups compared to the healthy group could be related to the presence of genetic variants for E. gingivalis rather than the immune status of the individuals.…”
Section: Discussionsupporting
confidence: 88%
“…Compared with the previous studies from different countries in which the microscopic method was used to identify E. gingivalis, more or less similar results were reported. Younis and Edamame [13] from Libya detected E. gingivalis in 17% out of 100 examined samples; Al-Najar and Adnan [14] from Iraq reported a prevalence rate of 28% for E. gingivalis among their participants; in addition, Hassan et al [15] from Egypt, reported a prevalence rate of 25.8% among120 participants. On the other hand, in DNA-based studies, more higher prevalence rates were observed.…”
Section: Discussionmentioning
confidence: 99%